2012
DOI: 10.1371/journal.pone.0049700
|View full text |Cite|
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell-Derived Models to Investigate Human Cytomegalovirus Infection in Neural Cells

Abstract: Human cytomegalovirus (HCMV) infection is one of the leading prenatal causes of congenital mental retardation and deformities world-wide. Access to cultured human neuronal lineages, necessary to understand the species specific pathogenic effects of HCMV, has been limited by difficulties in sustaining primary human neuronal cultures. Human induced pluripotent stem (iPS) cells now provide an opportunity for such research. We derived iPS cells from human adult fibroblasts and induced neural lineages to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 34 publications
7
64
0
Order By: Relevance
“…Cells were reprogrammed with Sendai viral vectors expressing the transcription factors Sox2, c-Myc, Klf4, and Oct4. Following QC measures described earlier, 4 iPSCs were maintained in 6-well plates with the supplemented mTeSR TM 1 medium (Stem Cell Technologies) changed daily, allowing for manual cleaning of differentiated cells. The protocol was approved by the University of Pittsburgh Institutional Review Board and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were reprogrammed with Sendai viral vectors expressing the transcription factors Sox2, c-Myc, Klf4, and Oct4. Following QC measures described earlier, 4 iPSCs were maintained in 6-well plates with the supplemented mTeSR TM 1 medium (Stem Cell Technologies) changed daily, allowing for manual cleaning of differentiated cells. The protocol was approved by the University of Pittsburgh Institutional Review Board and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…A small fraction of neurons were GAD1 positive. 4 No dopaminergic neurons were observed following immunocytochemistry. A subpopulation of neurons stained for CALBINDIN (Fig.…”
Section: Outline Of Differentiation Protocol and Nomenclaturementioning
confidence: 97%
See 1 more Smart Citation
“…Permissivity increases with extended passaging of the cells (9). Recently, rosette-type neural stem cells (R-NSCs) and neural progenitor cells (NPCs) generated in vitro from induced pluripotent stem cells (iPSCs) were also used as models to study HCMV rep-lication in neural cells, and similar results were obtained (10). One difficulty in interpreting the results of these studies is that the cell populations were poorly characterized, contained cells at different neural developmental stages, and could not be stably maintained in culture.…”
mentioning
confidence: 70%
“…12 Two other studies used neural stem cells generated from human induced pluripotent stem (iPS) cells and reported that HCMV infection impaired neuronal differentiation. 13,14 In order to perform molecular investigations on the outcomes of HCMV infection on neural progenitor cells, we used a new model, highly neuronogenic neural stem cells from embryonic stem cells (NSCs) (Fig. 1).…”
Section: Modeling Hcmv Neuropathogenesismentioning
confidence: 99%